Constructing samples for characterizing household food security and for monitoring and evaluating food security interventions: theoretical concerns and practical guidelines: Technical guide: strengthening the household food security and nutritional aspects of IFAD poverty alleviation projects: developing operational methodologies for project design and monitoring - Carletto, Calogero (International Food Policy Research Institute, 1999)
Reliable information on household food security is a prerequisite for the accurate and effective design, monitoring, and evaluation of development projects. In part due to the commitment, on the part of many development agencies, to work in marginalized areas, this information is often either not available or grossly out-of-date. But collecting data is not a costless exercise. This guide discusses how random sampling techniques—methods that use some mechanism involving chance to determine which farms, households, or individuals are to be studied—can economize on the costs of gathering information while increasing the likelihood that it will be both accurate and available in a timely fashion.